(untitled) (Research, Society and Development, 2025)
Canine distemper is an infectious disease caused by the Morbillivirus virus. It has a high prevalence in carnivores, especially dogs (Canidae family). Its main symptoms include eye inflammation, fever, diarrhea, vomiting, lethargy, loss of appetite, difficulty breathing, and myoclonus. The diagnosis is made through anamnesis, clinical examination and complementary tests. There is no specific treatment for this disease; the therapeutic approach is symptomatic-palliative, varying according to the animal’s needs. This study aimed to report a clinical case of canine distemper, mentioning all its general aspects and evolution. The case involved a male Yorkshire Terrier, small size, 1 year and 8 months old. It presented to a veterinary clinic with his owner, exhibiting symptoms of dehydration, eye discharge, vomiting and whitish gums, having not eaten for two days. Its medical history included only two doses of the canine multivalent vaccine. Through clinical analysis combined with a complete blood count and rapid RT-PCR test, the final diagnosis was canine distemper. Due to its advanced stage, supportive therapy was implemented with saline solution, Enrofloxacin, Dipyrone, Bionew, Ornitil, Ondansetron and Diazepam. The animal did not respond positively to treatment and, due to its deterioration, euthanasia was chosen. Despite the correct diagnosis, the absence of specific treatment combined with the lack of vaccine protection led to the need for euthanasia. It is concluded that greater awareness among pet owners regarding the importance of vaccination schedules is necessary, as well as the need for further studies to develop better therapies.